Safety and efficacy of nabilone for acute chemotherapy‐induced vomiting prophylaxis in pediatric patients: A multicenter, retrospective review. Issue 12 (26th July 2018) - Polito, Samantha; MacDonald, Tamara; Romanick, Marcel; Jupp, Jennifer; Wiernikowski, John; Vennettilli, Ashlee; Khanna, Mila; Patel, Priya; Ning, Winnie; Sung, Lillian; Dupuis, L. Lee
Abstract: Objectives: To describe the safety and efficacy of nabilone given to pediatric patients to prevent acute chemotherapy‐induced nausea and vomiting (CINV). Methods: A multicenter, retrospective review of pediatric patients who received nabilone for acute CINV prophylaxis between December 1, 2010 and August 1, 2015 was undertaken. One course of nabilone was evaluated per patient. Adverse effects associated with nabilone use were noted. The proportion of patients who experienced complete acute chemotherapy‐induced vomiting (CIV) control during the acute phase was determined. The acute phase was defined as starting with the first chemotherapy dose and continuing until 24 h after administration of the last chemotherapy dose of the chemotherapy block. Results: One hundred ten eligible patients (median age: 14.0 years, range: 1.1–18.0 years; 65 male) were identified. Most (109/110) received nabilone plus a 5‐HT3 antagonist for CINV prophylaxis. Adverse effects associated with nabilone were experienced by 34% (37/110) of children. All were of CTCAE Version 4.03 Grade 2 or less. Sedation (20.0%), dizziness (10.0%), and euphoria (3.6%) were the most commonly reported adverse events. Nabilone was discontinued in 10 patients due to an adverse event. The proportions of patients receiving highly or moderately emetogenic chemotherapy who experienced complete acute CIV control were 50.6% (42/83) and 53.8% (14/26), respectively. Conclusion: Adverse events associated with nabilone were common but of minor clinical significance. Acute CIV control in children receiving nabilone as a part of their antiemetic regimen was poor. Future work should focus on implementation of guideline‐consistent CINV prophylaxis and treatment.